Training dogs to indicate synthetic pheromones from Plagionotus detritus, Coleoptera, Cerambycidae to detect living beetles - Apelqvist, Matilda (2022)
Using dogs to detect insects’ emitted volatiles is a non-invasive procedure, and a trained detection dog is potentially a fast and accurate method to search for saproxylic insects. The longhorn beetle Plagionotus detritus is categorized as Endangered in the Swedish Red List of Threatened Species. The beetle is difficult to detect and monitor with conventional survey methods. Studies indicate that the beetle can be monitored using pheromone traps. Pheromone works on large scale and using a detection dog might be a good complement. Performing the training of the dog on a synthetically reproduced scent from the beetle will not require access to live specimens of the endangered target species. In this study the potential for trained dogs to indicate synthetic pheromones from P. detritus to detect a living male beetle was examined. The dogs were first trained to indicate synthetic pheromone from P. detritus. The synthetic compounds used in the study were the two pheromone components of the P. detritus pheromone: (R)-3-hydroxy-hexan-2-one as the major component and (S)-2-hydroxy-octan-3-one as the minor component. Secondly, the dogs were taught to discriminate the target odour from similar decoys. Both compounds in the synthetic pheromone were used separately as decoys, in addition to three other compounds found in closely related Swedish longhorn beetle species, living in the same habitat. For the final test the synthetic pheromone was replaced with a living male beetle of P. detritus to determine if the dog trained to detect synthetic pheromone from P. detritus can recognize the scent from a living male beetle. The study was conducted on five dogs. The evaluation of a dog, the imprinting of the target scent, and the tests of the pheromone were carried out indoors for one day. All dogs managed to indicate the synthetic pheromone from P. detritus and learned to discriminate the decoys. Three of the dogs indicated the living male beetle in at least one out of three trials against synthetic decoys, and one dog indicated the beetle in three out of three trials. This method of indoor training on synthetics could be a valuable method for training dogs to detect endangered saproxylic insects in their habitat. This is promising for advancing the use of detection dogs for monitoring and protect endangered insects.